2013
DOI: 10.1556/comec.14.2013.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in foraging guild structure of forest breeding bird assemblages across three continents is related to habitat structure and foraging opportunities

Abstract: Comparisons of community structure across sites allow for the detection of convergent patterns and the selective forces that have produced them. In this study, we examined the foraging guild structure of birds breeding in forests on three continents-Europe, North America, and Australia, with largely phylogenetically distinct avifaunas. We examined two hypotheses: (1) the bird assemblages in the three geographically separated forested study sites should have similar foraging guild patterns to the extent to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
(74 reference statements)
2
19
0
Order By: Relevance
“…Absent from, or poorly represented in, the winter community considered in this paper are the nectar-feeder and aerial-forager/snatcher guilds recognized in the guild analyses of Holmes and Recher (1986) and Korňan et al (2013). The species forming these guilds in summer were either absent or present only in reduced numbers during winter.…”
Section: Australian Zoologist Volume 38 (1)mentioning
confidence: 89%
See 4 more Smart Citations
“…Absent from, or poorly represented in, the winter community considered in this paper are the nectar-feeder and aerial-forager/snatcher guilds recognized in the guild analyses of Holmes and Recher (1986) and Korňan et al (2013). The species forming these guilds in summer were either absent or present only in reduced numbers during winter.…”
Section: Australian Zoologist Volume 38 (1)mentioning
confidence: 89%
“…The analysis of Holmes and Recher (1986) included body weight with four guilds separated by size; large and small ground foragers, and large and small aerial foragers. By ignoring body weight the number of guilds is reduced to seven, which is the same as obtained by Korňan et al (2013) using different statistical procedures, but the same data, if body weight is also excluded from their analysis. The guilds identified by Korňan et al (2013) are the same as reported by Holmes and Recher (1986), but the species composition of the guilds identified differed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations